ANALISIS FAKTOR IBU YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA DI DESA SLARANG KECAMATAN KESUGIHAN CILACAP TAHUN 2017 - ., Sujianti; Subandi, Ahmad; ., Yuniariana (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Riskesdas 2007, 2010, 2013 shows that Indonesia still has nutritional problems. The prevalence of underweight (wasting) among toddlers is from 13.6% to 13.3% and decreases 12.1%. The prevalence trend of stunting is 36.8%, 35.6%, 37.2%. The prevalence of underweight is 18.4%, 17.9% and 19.6%, respectively. Nutrition disorders in children under five are the cumulative effects of various factors. Indirect factors which are associated with the mother are levels and knowledge about nutrition, family income, and environmental sanitation. Data from the Public Health Office of Cilacap Regency in 2016 ranked Cilacap as the 2nd malnutrition cases of toddlers in Central Java with the number of 77 cases. Slarang village has 1059 children under five years old, where 5% of them have less nutrition (48 cases) in February 2017. This research aimed to know the factors of mother associated with nutritional status of toddlers in Slarang village, Kesugihan, Cilacap 2017. A descriptive design and cross-sectional time-based study was conducted. The data collected was primary data using questionnaires included age, education, occupation, birth spacing, number of children and number of toddlers .Univariable data was used to explain the rotation of each table and bivariable using chi square was used to analyze the data. The result of the study indicated the factors of mother associated with nutritional status of toddlers. The results showed that mother’s factor which related to the nutritional status of toddlers was the age. Education, employment, birth spacing, number of children under five and number of children were not related to the nutritional status of toddlers in Slarang village, Kesugihan district in 2017.  Keywords: mother‘s factors analysis, nutritional status, toddlers